2010
DOI: 10.1111/j.1537-2995.2010.02714.x
|View full text |Cite
|
Sign up to set email alerts
|

White blood cell inactivation after treatment with riboflavin and ultraviolet light

Abstract: Functional white blood cells (WBCs) in blood components may be responsible for a number of adverse transfusion effects, including transfusion-associated graft-versus-host disease (TA-GVHD), alloimmunization, and alloimmune platelet (PLT) refractoriness. TA-GVHD occurs when functional lymphocytes are transfused into a patient who is unable to mount an immune response to the human leukocyte antigen (HLA) due to HLA compatibility or immunosuppression. Alloantibodies against HLA antigens on donor WBCs and PLTs are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 49 publications
5
60
0
3
Order By: Relevance
“…However, recent analyses have demonstrated that PRT-treated blood products may actually reduce the overall health care costs [21] and the duration of hospital stay associated with post-transfusion care for some patients. Due to the ability of the Mirasol PRT treatment to inactivate all remaining leukocytes in a product that mediate graft-versus-host disease (GvHD) [22], it can be used as an alternative to γ-irradiation. γ-Irradiation is both costly and cumbersome for hospitals to maintain and operate [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent analyses have demonstrated that PRT-treated blood products may actually reduce the overall health care costs [21] and the duration of hospital stay associated with post-transfusion care for some patients. Due to the ability of the Mirasol PRT treatment to inactivate all remaining leukocytes in a product that mediate graft-versus-host disease (GvHD) [22], it can be used as an alternative to γ-irradiation. γ-Irradiation is both costly and cumbersome for hospitals to maintain and operate [23].…”
Section: Discussionmentioning
confidence: 99%
“…Gamma irradiation (25-30 Gy) is currently the accepted standard of care for transfusions in immunocompromised patients or patient populations that are particularly susceptible to TA-GvHD. Mirasol treatment is as effective as gamma irradiation in inactivating leukocytes [36,37], providing an alternative to gamma irradiation. Additional…”
Section: Introductionmentioning
confidence: 99%
“…Other benefits are those derived from the inactivation of leukocytes that are not removed by leukoreduction [10]. Essentially, preventing alloimmunization of leukocyte-borne antigens, and eliminating the risk of transfusion-associated graft-versus-host disease are important advantages of riboflavin- and UV light-based PRT [11,12,13]. …”
Section: Discussionmentioning
confidence: 99%